Increased tyrosine hydroxylase expression accompanied by glial changes within the non-lesioned hemisphere in the 6-hydroxydopamine model of Parkinson's disease - Schlachetzki, Johannes; Marxreiter, Franz; Regensburger, Martin; Kulinich, Anna; Winner, Beate; Winkler, Jürgen (Restorative Neurology and Neuroscience, 2014)
Parkinson's disease (PD) is characterized by striatal synaptic deafferentation followed by dopaminergic cell death in the substantia nigra pars compacta. Not only degenerative, but also regenerative, compensatory changes at distant sites of the primary lesion may occur in PD. The aim of the study was to analyze the temporal pattern of axonal and glial responses over a time course of six weeks post-lesioning.For this aim, 6-hydroxydopamine (6-OHDA) was injected unilaterally into the medial forebrain bundle and both lesioned and non-lesioned striata were analyzed.We detected increased tyrosine hydroxylase (TH) immunoreactivity within the non-lesioned striatum six weeks after injection indicative either of increased TH expression or compensatory neuritic changes. An increased number of microglial cells was present in both lesioned and unlesioned striata. There was no obvious change in microglial phenotype or in pro-inflammatory cytokine gene expression within the striatum without any apparent switch into a pro-inflammatory phenotype. No changes were observed in the number of mature oligodendrocytes.This temporal pattern shows, that the non-lesioned striatum undergoes profound changes, involving increased TH expression accompanied by a glial response. A better understanding of this complex interplay of neuronal as well as glial components not only within the lesioned, but also non-lesioned striatum may help to restore local neural circuits in PD.
EVALuna2:25334